Bridging the sustainability gap: Unraveling the interplay of sustainability disclosure and cost of debt - Muhammad Mubeen; Hafiz Muhammad Arslan; Khurram Ashfaq; Asad Nisar; Hafiz Azeem; Adil Riaz (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2024)
In the contemporary corporate world, environmental responsibility has elevated the importance of sustainability disclosures and their impact on the cost of debt. Conducting the first comprehensive review in this domain, this study analyzed 76 articles from 2008 to 2022 using the Biblioshiny package in the R program (for bibliometric visualization) and VOSviewer version (for bibliographic coupling), employing strict inclusion criteria based on the PRISMA protocol. The investigation was done to check the influence of sustainability disclosures on the cost of debt, including environmental and social dimensions. Additionally, it synthesized perspectives from lending institutions, corporate governance, earnings management, sustainable business practices, and GHG / Carbon emissions in this relationship. The study has also synthesized the literature with conclusion that high-quality environmental and social disclosures with sustainable practices and reduced carbon emission significantly reduce a firm's cost of debt by minimizing perceived risks, and enhancing reputation, credibility and demand from socially responsible investors. Active engagement in CSR, sustainable practices, proper governance, and stakeholder orientation further contribute to lower the cost of debt. Conversely, inadequate disclosure quality, high carbon emissions, poor environmental records and negative media attention may increase borrowing costs and environmental penalties. This study will help CFOs to develop tailored sustainability strategies in optimization of their cost of debt resulting in higher financial performance. Results of this study are also helpful for policymakers, regulators, financial analysts, auditors, and investors.
Keywords: 330; Sustainability disclosures; cost of debt; sustainability assurance; lending institutions; corporate governance; sustainable business practices; carbon emission; ESG